2009
DOI: 10.4037/ajcc2009672
|View full text |Cite
|
Sign up to set email alerts
|

Living With Depressive Symptoms: Patients With Heart Failure

Abstract: Background Patients with heart failure often experience depressive symptoms that affect health-related quality of life, morbidity, and mortality. Researchers have not described the experience of patients with heart failure living with depressive symptoms. Understanding this experience will help in developing interventions to decrease depressive symptoms.Objective To describe the experience of patients with heart failure living with depressive symptoms.Methods This study was conducted by using a qualitative des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 27 publications
4
59
2
2
Order By: Relevance
“…Impact of positive encounters with healthcare professionals on self-estimated ability to return to work OR, 95% CI, p Impact of positive encounters with social insurance officers on selfestimated ability to return to work OR, 95% CI, p 3, .9-2.0, .192 by the limitations brought by the condition (Dekker et al, 2009;Moser et al, 2013), implying reduced self-esteem and a changed self-image . Previously, this discrepancy has been described in terms of 'Loss and Disappointment' (Moser et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Impact of positive encounters with healthcare professionals on self-estimated ability to return to work OR, 95% CI, p Impact of positive encounters with social insurance officers on selfestimated ability to return to work OR, 95% CI, p 3, .9-2.0, .192 by the limitations brought by the condition (Dekker et al, 2009;Moser et al, 2013), implying reduced self-esteem and a changed self-image . Previously, this discrepancy has been described in terms of 'Loss and Disappointment' (Moser et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been described that depression is associated with HF, especially in younger persons and in women (Dekker, Peden, Lennie, Schooler, & Moser, 2009;Moraska et al, 2013;Sacco et al, 2014). In addition, depression has been described as…”
Section: Introductionmentioning
confidence: 96%
“…[38] Being religious and accepting the diagnosis is linked to positive experience with HF and enhances the meaning of life, [4] whereas spirituality was an essential way to manage the depressive symptoms, and the patients who were involved in religious practice were able to recover from depression faster than the non-religious. [39] While another study showed that being religious, faithful and remaining hopeful is not a common coping strategy. [14] Our study revealed that HF patients in Bahrain depend greatly on their religious beliefs to cope, however, for some the emphasis on religious beliefs led them to believe that they did not need to make lifestyle changes and to comply with treatment regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that individuals with greater positive thinking have a better capability to deal with stressful situations, better adaptive functioning, as well as an enhanced quality of life in various populations (Dekker, Peden, Lennie, Schooler, & Moser, 2009;Jung et al, 2007;Lightsey & Boyraz, 2011). Positive thinking is a cognitive process that helps individuals to create hopeful images, find favorable solutions to problems and produce an overall bright outlook on life (Bekhet & Zauszniewski, 2013).…”
Section: Introdutionmentioning
confidence: 97%